2005
DOI: 10.1055/s-2005-871258
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Properties of Extracts, Fractions and Lignans Isolated fromPhyllanthus amarus

Abstract: This study assessed the anti-inflammatory effect of the extracts and purified lignans obtained from Phyllanthus amarus. Given orally, the hexane extract (HE), the lignan-rich fraction (LRF), or the lignans phyltetralin, nirtetralin, niranthin, but not hypophyllanthin or phyllanthin, inhibited carrageenan (Cg)-induced paw oedema and neutrophil influx. The HE, the LRF or nirtetralin also inhibited the increase of IL1-beta tissue levels induced by Cg. Furthermore, bradykinin (BK)-, platelet activating factor (PAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 20 publications
1
60
1
2
Order By: Relevance
“…Phyltetralin, nirtetralin and niranthin exhibited anti-inflammatory activity by inhibiting carrageenan-induced paw oedema and neutrophil influx (Kassuya et al 2005). Huang et al (2003) reported the anti-HBsAg and anti-HBeAg activities of niranthin and nirtetralin and the compounds suppressed HBsAg and HBeAg expression effectively at a non-cytotoxic concentration of 50 mM.…”
Section: Lignansmentioning
confidence: 99%
“…Phyltetralin, nirtetralin and niranthin exhibited anti-inflammatory activity by inhibiting carrageenan-induced paw oedema and neutrophil influx (Kassuya et al 2005). Huang et al (2003) reported the anti-HBsAg and anti-HBeAg activities of niranthin and nirtetralin and the compounds suppressed HBsAg and HBeAg expression effectively at a non-cytotoxic concentration of 50 mM.…”
Section: Lignansmentioning
confidence: 99%
“…It has been reported to exhibit marked anti-hepatitis B virus surface antigen activity both in in vivo [1][2][3] and in vitro studies [4,5]. Furthermore, the plant has been reported to possess antibacterial [6], anticrustacean [7], antiviral [8], anti-inflammatory [9], anticancerous [10], antidiabetic, and anticholesterol activities [11]. Different parts of plant are ethnobotanically reported to have various therapeutic activities such as expectorant, diaphoretic, and diuretic [12].…”
Section: Introductionmentioning
confidence: 99%
“…The popular uses of Phyllanthus species reported the treatment of dysentery, gonorrhea, urinary discharges, kidney and bladder stones (Unander et al, 1995). Besides its traditional use, other pharmacological properties were also investigated such as hypoglycemic (Hukeri et al, 1988;Navarro et al, 2004), anti-hepatotoxic (Prakash et al, 1995;Naaz et al, 2007), antimalarial (Tona et al, 1999), antinociceptive (Santos et al, 1995), antiinflammatory (Kassuya et al, 2003(Kassuya et al, , 2005(Kassuya et al, , 2006, antiviral (Ogata et al, 1992;Qian-Cutrone et al, 1996), hypolipidemic (Khanna et al, 2002), antihyperuricemic (Murugaiyah & Chan, 2009) and as wound healing (Shanbhag et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Most pharmacological properties for P. niruri have been reported using the whole plant, since Phyllanthus species are commonly small herbs and they are employed in this manner in folk medicine, and several actives constituents that have been identified and isolated from P. niruri, such as flavonoids, alkaloids, terpenes and lignans (Calixto et al, 1998;Kassuya et al, 2003Kassuya et al, , 2005Kassuya et al, , 2006. However, the Brazilian Pharmacopoea Comission published a Monograph describing the aerial parts as the official drug (Farmacopéia Brasileira, 2003) and gallic acid as one of its chemical markers.…”
Section: Introductionmentioning
confidence: 99%